2015
DOI: 10.5114/pr.2015.54036
|View full text |Cite
|
Sign up to set email alerts
|

Endovenous laser ablation of incompetent calf perforating veins does not prevent recurrence of venous ulcers in patients with post-thrombotic syndrome

Abstract: Aim of the study was to assess efficacy of endovenous laser ablation of incompetent calf perforators in patients with post-thrombotic syndrome in preventing recurrence of venous leg ulcers. Material and methods:We conducted a single-centre prospective randomized study. Patients with healed venous ulcers were randomly assigned either to endovenous laser ablation of incompetent calf perforators together with compression therapy (n = 31), or to compression alone (n = 32). We used a 940 nm laser system and under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In this issue of Phlebological Review Zolotukhin et al [1] present the results of their study on recurrence of venous leg ulcers in post-thrombotic patients after endovenous laser ablation of incompetent lower leg perforators. They have found that not only the recurrence rate of these perforators was very high, but also that the procedure did not reduce the ulcer recurrence.…”
mentioning
confidence: 99%
“…In this issue of Phlebological Review Zolotukhin et al [1] present the results of their study on recurrence of venous leg ulcers in post-thrombotic patients after endovenous laser ablation of incompetent lower leg perforators. They have found that not only the recurrence rate of these perforators was very high, but also that the procedure did not reduce the ulcer recurrence.…”
mentioning
confidence: 99%